2013
DOI: 10.1111/jmi.12102
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton microscopic imaging of human normal and cancerous oesophagus tissue

Abstract: SummaryIn this paper, microstructures of human oesophageal submucosa are evaluated using multiphoton microscopy, based on two-photon excited fluorescence and second harmonic generation. The content and distribution of collagen, elastic fibers and cancer cells in normal and cancerous submucosa layer have been distinctly obtained and briefly discussed. The variation of these components is very relevant to the pathology in oesophagus, especially in early oesophageal cancer. Our results further indicate that the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In stark contrast to the mentioned study, Xiong et al [117] found that collagen appeared broadened, integrated and well distributed in normal skin, while it was fragmented, reduced and disordered in squamous cell carcinoma (SCC) and basal cell carcinoma (BCC) of human skin. Loss of collagen associated SHG was also observed in neoplasia of oropharynx, [118], lungs [119], rectum [75], oesophagus [120], while SHG was observed to be absent in breast carcinoma [70]. This disparity could arise due to variation in species, related organ or the tumour microenvironment involved for that specific cancer subtype.…”
Section: Shg Based Quantitative and Morphometric Analysis Of Collagenmentioning
confidence: 98%
“…In stark contrast to the mentioned study, Xiong et al [117] found that collagen appeared broadened, integrated and well distributed in normal skin, while it was fragmented, reduced and disordered in squamous cell carcinoma (SCC) and basal cell carcinoma (BCC) of human skin. Loss of collagen associated SHG was also observed in neoplasia of oropharynx, [118], lungs [119], rectum [75], oesophagus [120], while SHG was observed to be absent in breast carcinoma [70]. This disparity could arise due to variation in species, related organ or the tumour microenvironment involved for that specific cancer subtype.…”
Section: Shg Based Quantitative and Morphometric Analysis Of Collagenmentioning
confidence: 98%
“…found that malignant tissue had more ordered and regularly packed collagen as compared to normal tissue (Kirkpatrick et al ., ; Nadiarnykh et al ., ). Moreover, it was also observed that there would be a loss of collagen in neoplasia of lungs, rectum, oropharynx and oesophagus (Meyer et al ., ; Xu et al ., ; Chen et al ., ; Yan et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Provenzano et al reported that collagen density may promote mammary tumour initiation and progression (Provenzano et al, 2008), Xiong et al showed that collagen was fragmented and disordered in squamous cell carcinoma as well as basal cell carcinoma of human skin, but it was broadened and well distributed in normal skin (Xiong et al, 2011), whereas Nadiarnykh et al and Kirkpatrick et al found that malignant tissue had more ordered and regularly packed collagen as compared to normal tissue (Kirkpatrick et al, 2007;Nadiarnykh et al, 2010). Moreover, it was also observed that there would be a loss of collagen in neoplasia of lungs, rectum, oropharynx and oesophagus (Meyer et al, 2013;Xu et al, 2013;Chen et al, 2014;Yan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Scanning with a fine-focused laser beam makes it possible to obtain images that reflect the peculiarities of the collagen folding in the tissue in detail. Nonlinear microscopy in SHG detection regime is now used in dermatology, 15 ophthalmology, 16 oncology, 17,18 atherosclerotic vascular disease studies, 19,20 and diseases with abnormal accumulation of collagen in tissues and organs. 21 The principle of OCT is the measurement of the echo time delay and magnitude of backscattered light.…”
mentioning
confidence: 99%